Rural Finance Policies 3 - Product innovation for the poor: the role of microfinance - Zeller, Manfred (International Food Policy Research Institute, 2000)
This policy brief reviews evidence and draws lessons regarding the role of microfinance for income and consumption smoothing by the poor, and highlights potential areas for product innovation by the microfinance sector to address the demand for financial services for income and consumption smoothing.... MFIs, especially if they seek to benefit the poor, should concentrate more effort on services that can mitigate risks. A number of innovative MFIs offer financial products that respond to risks, such as flexible saving, services that permit prompt withdrawals, consumption credit, and even explicit health and life insurance.